Methylene Blue-Loaded Dissolving Microneedles: Potential Use in Photodynamic Antimicrobial Chemotherapy of Infected Wounds - Ester Caffarel-Salvador; Mary-Carmel Kearney; Rachel Mairs; Luigi Gallo; Sarah A. Stewart; Aaron J. Brady; Ryan F. Donnelly (MDPI AG, 2015)
Photodynamic therapy involves delivery of a photosensitising drug that is activated by light of a specific wavelength, resulting in generation of highly reactive radicals. This activated species can cause destruction of targeted cells. Application of this process for treatment of microbial infections has been termed "photodynamic antimicrobial chemotherapy" (PACT). In the treatment of chronic wounds, the delivery of photosensitising agents is often impeded by the presence of a thick hyperkeratotic/necrotic tissue layer, reducing their therapeutic efficacy. Microneedles (MNs) are an emerging drug delivery technology that have been demonstrated to successfully penetrate the outer layers of the skin, whilst minimising damage to skin barrier function. Delivering photosensitising drugs using this platform has been demonstrated to have several advantages over conventional photodynamic therapy, such as, painless application, reduced erythema, enhanced cosmetic results and improved intradermal delivery. The aim of this study was to physically characterise dissolving MNs loaded with the photosensitising agent, methylene blue and assess their photodynamic antimicrobial activity. Dissolving MNs were fabricated from aqueous blends of Gantrez® AN-139 co-polymer containing varying loadings of methylene blue. A height reduction of 29.8% was observed for MNs prepared from blends containing 0.5% w/w methylene blue following application of a total force of 70.56 N/array. A previously validated insertion test was used to assess the effect of drug loading on MN insertion into a wound model. Staphylococcus aureus, Escherichia coli and Candida albicans biofilms were incubated with various methylene blue concentrations within the range delivered by MNs in vitro (0.1-2.5 mg/mL) and either irradiated at 635 nm using a Paterson Lamp or subjected to a dark period. Microbial susceptibility to PACT was determined by assessing the total viable count. Kill rates of >96%, were achieved for S. aureus and >99% for E. coli and C. albicans with the combination of PACT and methylene blue concentrations between 0.1 and 2.5 mg/mL. A reduction in the colony count was also observed when incorporating the photosensitiser without irradiation, this reduction was more notable in S. aureus and E. coli strains than in C. albicans.